GAMBARAN RASA SYUKUR PADA WARGA BINAAN PEMASYARAKATAN LANJUT USIA DI RUTAN KELAS IIB BOYOLALI - Tasya Maria Monica Giupy; Emannuel Satyo Yuwono (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2026)
The increasing number of elderly inmates (WBP—Warga Binaan Pemasyarakatan) in Indonesia has become an important concern in the field of psychological well-being. Elderly individuals serving prison sentences face various challenges, such as restrictions on freedom, declining physical condition, and the risk of social isolation, all of which can diminish their vitality and emotional well-being. In such circumstances, gratitude plays a crucial role as an inner source of strength that helps individuals accept their situation, foster psychological resilience, and find meaning in life amid limitations. This study aims to describe the experience of gratitude among elderly inmates at the Class IIB Boyolali Detention Center (Rutan). The research employed a qualitative phenomenological approach involving three participants aged 60 years and above, selected through purposive sampling. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using thematic analysis to uncover the subjective meanings of the participants’ experiences of gratitude. The results show that gratitude serves as a psychological and spiritual strength that enables elderly inmates to live their prison life more peacefully, accept their circumstances with sincerity, and maintain hope and optimism for the future. These findings provide valuable insights for detention center staff, counselors, and families to develop rehabilitation and mentoring programs that focus on strengthening spiritual values, fostering gratitude, and enhancing social support to improve the psychological well-being of elderly inmates in correctional settings. Keywords: gratitude, elderly, inmates